Spectral model with a regional focus (MAUSAM, 1989)
A global spectral model with selective high resolution region Is appropriate for the study of a sharp local weather system if it is not very sensitive to the atmospheric state outside a limited active region. If the linear dimension of the resolution required is 1 and the area of active region is A then one finds that an adequate spectral model has the following features: (a) the model pole is moved away from the geographical north and re-located In the Vicinity of the weather system under study, (b) the set of new spherical harmonics ymn as basis functions should have the parallelogrammic truncated range | m |